Goodbye or Identify: Detrimental Effects of Downsizing on Identification and Survivor Performance - van Dick, Rolf; Drzensky, Frank; Heinz, Matthias (Frontiers in Psychology, 2016)
Research shows that after layoffs, employees often report decreased morale and performance which has been coined the survivor syndrome. However, the mechanisms underlying this effect remain underexplored. The purpose of the paper is to show that reduced organizational identification can serve as an explanation for the survivor syndrome. We conducted a laboratory experiment, in which participants work as a group of employees for another participant who acts as employer. In the course of the experiment, the employer decides whether one of his or her employees should be laid off or not. Mediation analysis supports a social identity-based explanation for the emergence of the survivor syndrome: downsizing causes lower identification with the employer which in turn relates to lower performance of employees.